Effectiveness Of Android Based Antenatal Care Application To Enhance Antenatal Care Adherence And Pregnant Mothers Health: A Literature Review - Tanberika, Fajar Sari; Sansuwito, Tukimin Bin; Hassan, Hafizah Che (International Journal of Health Sciences, 2023)
Introduction: Even though antenatal care checks are incredibly crucial for monitoring the health development of both mothers and newborns, the reality is that a significant number of pregnant women do not go to their appointments as much as is recommended. This is because pregnant women are frequently tardy in doing prenatal care checks since there is a lack of information regarding the significance of antenatal checks for the development of health. Experts are attempting to progress in the health sector by using mobile devices in health services to monitor antenatal care (ANC) for pregnant women. This is being done in light of the rapidly evolving technology of the 4.0 age. This application will serve to remind pregnant women of the scheduled examination appointments suggested for them. Additionally, it can potentially improve health services for pregnant women and identify issues that may arise during pregnancy. Methods: Conduct a systematic data analysis by examining existing research findings on the efficacy of Android-based antenatal care applications in enhancing adherence to antenatal care and improving maternal health. Articles about the specified theme were chosen from 2018 to 2023 using electronic databases like Science Direct, PubMed, Google Scholar, and open knowledge maps for the search. The researcher employed the PRISMA methodology to analyze the literature study comprehensively. Results: Of 184 papers, ten studies were deemed suitable and thoroughly examined and studied regarding their research objectives, samples, methodology, and findings with keywords Antenatal Care Application, Android, Antenatal Care Adherence, and Pregnant Mothers Health. The selection process for this study is presented in Figure 1. Conclusion: An Antenatal Care Application based on Android has the potential to enhance compliance with Antenatal Care, enhance the health of pregnant women, augment maternal knowledge and behavior, improve health services for pregnant women, and facilitate the detection of pregnancy issues.